State Plan Proposals Eighth Five Year Plan (1990-95) and Annual Plan (1991-92) Volume-II Government of West Bengal - Planning Commission (Planning Commission, 1990)
Outlay and Expenditure During the Seventh Plan Physical Target and Achievement During the Seventh Plan Draft Eighth Plan (1990-95)- Proposals for Programmes/Projects Maximising Benefits From the Existing Capacity(as on 31.3.90) Draft Eighth Plan(1990-95) and Annual Plan 1990-91 and 1991-92 - Outlays by Heads of Development Draft Eighth Plan - Statement Regarding Externally Aided Projects Tribal Sub-Plan (TSP)-Financial Outlays/Physical Targets for 8th Plan and 1990-91 and 1991-92 Annual Plans Statement Regarding Employment (Scheme-Wise) In the 7th/8th Plan With the Corresponding Figures of Expenditure /Outlay Draft Eighth Plan(1990-95) and Annual Plan 1990-91 and 1991-92 - Minimum Needs Programme- Outlay and Expenditure Draft Eighth Plan (1990-95) and Annual Plan 1990-91 and 1991 -92 - Minimum Needs Programme- Target and Achievement.
Government of West Bengal, Development and Planning Department